Kesalahan Siswa Sekolah Menengah Atas dalam Menyelesaikan Tes Literasi Statistis Serupa Asesmen Kompetensi Minimum (AKM) - Putri, Cyndana Kartika; Juandi, Dadang; Kurniawan, Surya; Sukri, Sukri (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
The importance of students' mastery of statistics is supported by the inclusion of this material in the mathematics curriculum since primary and secondary education. The role of statistics itself has penetrated into various professions and fields of science. Regarding statistical mastery students need to have statistical literacy skills in the form of basic skills in reading graphs, graph titles or themes, giving meaning to units of graphs, finding certain values or units, determining maximum and minimum values or the difference between the two. This study aims to describe students' errors in solving statistical literacy test similar to minimum competency assessment or asesmen kompetensi minimum (in Indonesian) based on the Kastolan stages. The type of this study is qualitative research with a case study design. The subjects of this research were 5 students of grade 11, a senior high school in Banjarbaru, South Borneo, selected using purposive sampling technique. Data were collected using tests and interviews. During the study, it was found that errors made by students include conceptual errors, procedural errors, and technical errors. Students' errors in solving statistical literacy test can have an impact on their daily life when they are dealing with data. Moreover, errors made by students when solving problems can be an early sign that there are learning obstacles experienced by students.